Xác suất xuất hiện động đất mạnh ở Việt Nam theo bài toán mô hình thời gian - Magnitude - Hải, Đặng Thanh (Vietnam Journal of Earth Sciences, 2007)
The probability of strong earthquake occurrences in Vietnam territory based on the Time- Magnitude predictable model